2005
DOI: 10.1111/j.1467-9280.2005.01614.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypnotic Disgust Makes Moral Judgments More Severe

Abstract: Highly hypnotizable participants were given a posthypnotic suggestion to feel a flash of disgust whenever they read an arbitrary word. They were then asked to rate moral transgressions described in vignettes that either did or did not include the disgust-inducing word. Two studies show that moral judgments can be made more severe by the presence of a flash of disgust. These findings suggest that moral judgments may be grounded in affectively laden moral intuitions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
525
9
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 708 publications
(559 citation statements)
references
References 17 publications
15
525
9
10
Order By: Relevance
“…As such, the current results are also consistent with the proposed role of emotion in deontological judgments (Schnall et al, 2008;Van Dillen et al, 2012;Wheatley and Haidt, 2005). More specifically, the successful induction of avoidance-related emotions (e.g., disgust or fear) may lead to deontological moral judgments (Harle and Sanfey, 2010;Ugazio et al, 2012).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…As such, the current results are also consistent with the proposed role of emotion in deontological judgments (Schnall et al, 2008;Van Dillen et al, 2012;Wheatley and Haidt, 2005). More specifically, the successful induction of avoidance-related emotions (e.g., disgust or fear) may lead to deontological moral judgments (Harle and Sanfey, 2010;Ugazio et al, 2012).…”
Section: Discussionsupporting
confidence: 78%
“…Although future work is required to explore these effects, we suggest that the perception of fear in specific individuals may lead to an aversion to harming those individuals even when doing so may lead to saving other people, as in high-conflict scenarios (Crockett et al, 2010). On the other hand, low-conflict scenarios (e.g., causing harm for selfish benefit) may trigger moral disgust (Ugazio et al, 2012;Wheatley and Haidt, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research in psychology has examined, on the one hand, the effects of authority on obedience and norm compliance (Milgram, 1963), in-group/out-group effects on moral behavior (Tajfel et al, 1971), and the consequences of emotional cues on people's normative judgments (Schnall et al, 2008;Wheatley and Haidt, 2005). On the other hand, research studies on humans and nonhuman primates have shown that both species tend to adjust their behavior and beliefs toward others in their social circles (Cialdini and Goldstein, 2004;Whiten, Horner and de Waal, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Gazzaniga, 2005;Greene, Sommerville, Nystrom, Darley, & Cohen, 2001;Haidt, 2001;Inbar, Pizarro, Knobe, & Bloom, 2009;Mikhail, 2007;Moll, et al, 2005;Wheatley & Haidt, 2005). The majority of these studies focus on participants' negative evaluations of moral violations, for instance, hitting people with trolleys, breaking promises, distributing resources unfairly, and eating dead pets (Borg, Hynes, Van Horn, Grafton, & Sinnott-Armstrong, 2006;Cushman, 2008;Greene, Nystrom, Engell, Darley, & Cohen, 2004;Hauser, Cushman, Young, Jin, & Mikhail, 2007;Hsu, Anen, & Quartz, 2008).…”
Section: Introductionmentioning
confidence: 99%